The Microbiome and Emerging Pathogens in Cystic Fibrosis and Non–Cystic Fibrosis Bronchiectasis - Green, Heather; Jones, Andrew M. (Seminars in Respiratory and Critical Care Medicine, 2015)
Chronic pulmonary sepsis is the predominant cause of morbidity for patients with cystic fibrosis (CF) and non-CF bronchiectasis. Previously it was thought that respiratory infection in these patients was mostly limited to a very small number of typical pathogens; however, in recent years there have been increasing reports of infection with other emerging potential pathogens including Burkholderia, Stenotrophomonas, Achromobacter, Ralstonia, Pandoraea, nontuberculous mycobacteria, and fungal species. Furthermore, culture-independent methodologies have established that the lungs of patients with CF and non-CF bronchiectasis comprise mixed microbiological communities of aerobic and anaerobic bacteria, fungal and viral species, collectively referred to as the lung microbiome. This article addresses the clinical relevance of emerging pathogens and the lung microbiome in CF and non-CF bronchiectasis.
Keywords: cystic fibrosis; non-CF bronchiectasis; microbiology; emerging pathogens; microbiome